Geochemical composition of galena and its implication for Zn-Pb deposit type classification - Shihui Zhang; Qingwen Zeng; Baoshan Li; Yunfeng Zhang; Min Hu; Fan Yu; Qian Zhang; Zifeng He; Qihai Shu (Journal of Geochemical Exploration, 2026)

ALYREF expression correlated with upregulated YBX1 and HIF1α, contributing to cell migration in gastric cancer - Yujie Yuan; Jiaqi Qiu; Wenqing Tang; Xiaohui Shen; Hui Sun; Shihui Shu; Qiong Wang; Hong Fan (Tissue and Cell, 2026)

SETD2 inhibited T-cell acute lymphocytic leukemia invasion and infiltration by inhibiting the JAK/STAT pathway - Ling Qiu; Shihui Ren; Mengjiao Li; Baitao Dou; Dan Chen; Nan Zhang; Jiao Cai; Hao Yao; Fangyi Fan (Molecular and Cellular Biochemistry, 2026)

Adjunctive Human Urinary Kallidinogenase Enhances the Cognitive and Hemodynamic Outcomes of Anterior Circulation Stenting - Liuting Hu; Fan Yang; Wenjin Shang; Jing Yang; Xinran Chen; Shuangquan Tan; Hongbing Chen; Jian Zhang; Shihui Xing; Yuhua Fan (Translational Stroke Research, 2025)

Emulsifier is beneficial for declining dietary lipid requirement of aquatic crustaceans by accelerating the absorption, transport and deposition of lipids: A case study in mud crab (Scylla paramamosain) - Zihao Ye; Jinjin Liu; Shihui Cui; Jing Chen; Mengyao Tang; Chaojia Chen; Yifang Xu; Ziyi Wang; Yuan Huang; Shaowei Zhai; Ziping Zhang; Chao Fan; et al. (Animal Feed Science and Technology, 2025)

Predicting the impacts of climate change on the geographic distribution of moso bamboo in China based on biomod2 model - Rui Gu; Songpo Wei; Jiarui Li; Shihui Zheng; Zhiteng Li; Guanglu Liu; Shaohui Fan (European Journal of Forest Research, 2024)

Soft template-induced self-assembly strategy for sustainable production of porous carbon spheres as anode towards advanced sodium-ion batteries - Dingyue Zhang; Gang Huang; Hao Zhang; Ziqiang Zhang; Yong Liu; Fan Gao; Zhoutai Shang; Caiqin Gao; Yuhan Zhou; Shihui Fu; Jingjiang Wei; Mauricio Terrones; et al. (Chemical Engineering Journal, 2024)

A Ce/hopcalite catalyst for low-temperature oxidation of CO:Preparation, performance and mechanism - Xiaohui Fan; Shihui Ma; Min Gan; Zhiyun Ji; Zengqing Sun; Lincheng Liu (Chemical Engineering Journal, 2024)

Review on CO terminal treatment technologies in steel industry - Xiaohui Fan; Shihui Ma; Min Gan; Zhiyun Ji; Zengqing Sun; Lincheng Liu (Journal of Cleaner Production, 2023)

Fast and sensitive graphene oxide‐DNAzyme‐based biosensor for Vibrio alginolyticus detection - Xueqing Tian; Jinfei Hu; Tong Wei; Wen Ding; Qingzhen Miao; Zhe Ning; Shihui Fan; Hangjie Wu; Jing Lu; Mingsheng Lyu; Shujun Wang (Journal of Fish Diseases, 2022)
DNAzymes have been widely and effectively used for the detection of pathogenic bacteria, which pose a serious public health threat. However, the rapid and cost‐effective detection of such bacteria remains a major challenge. In this study, we successfully selected Vibrio alginolyticus ‐specific DNAzymes. The activity of the candidates was assessed via fluorescence intensity and gel electrophoresis. The DNAzyme DT1 had a detection limit of 31 CFU/ml for V. alginolyticus and exhibited high specificity. Graphene oxide (GO) was used to develop a DNAzyme‐based fluorescent sensor for the detection of V. alginolyticus , which significantly improved detection performance and shortened the reaction time as little as 10 s. The proposed method was then validated using crab, shrimp, fish, clam, and oyster samples. This study thus provides a new method for the rapid and sensitive detection of V. alginolyticus .

Is Cerebral Amyloid-β Deposition Related to Post-stroke Cognitive Impairment? - Fubing Ouyang; Zimu Jiang; Xinran Chen; Yicong Chen; Jiating Wei; Shihui Xing; Jian Zhang; Yuhua Fan; Jinsheng Zeng (Translational Stroke Research, 2021)

Quantitative proteomic and lipidomics analyses of high oil content GmDGAT1-2 transgenic soybean illustrate the regulatory mechanism of lipoxygenase and oleosin - Yang Xu; Fan Yan; Yajing Liu; Ying Wang; Han Gao; Shihui Zhao; Youcheng Zhu; Qingyu Wang; Jingwen Li (Plant Cell Reports, 2021)

Solution structure and backbone dynamics for S1 domain of ribosomal protein S1 from Mycobacterium tuberculosis - Biling Huang; Shihui Fan; Yan Liu; Yufen Zhao; Donghai Lin; Xinli Liao (European Biophysics Journal, 2019)

Therapeutic effects of lactosyl derivative Gu-4 in a collagen-induced arthritis rat model - Jie Fan; Huiting Zhou; Shihui Wang; Hailian Wang; Yushun Zhang; Yingtao Guo; Qing Li; Zhongjun Li; Zhihui Zhao (Glycoconjugate Journal, 2012)

Modulation of Brain Activities by Hierarchical Processing: A High-Density ERP Study - Shihui Han; Silu Fan; Lin Chen; Yan Zhuo (Brain Topography, 1999)